The high burden of alcoholic cirrhosis in privately insured persons in the United States. Issue 3 (20th May 2018) - Mellinger, Jessica L.; Shedden, Kerby; Winder, Gerald Scott; Tapper, Elliot; Adams, Megan; Fontana, Robert J; Volk, Michael L.; Blow, Frederic C.; Lok, Anna S.F.
Abstract : Alcoholic cirrhosis (AC) is a major cause of liver‐related morbidity and mortality in the United States. Rising rates of alcohol use disorders in the United States will likely result in more alcoholic liver disease. Our aim was to determine the prevalence, health care use, and costs of AC among privately insured persons in the United States. We collected data from persons aged 18‐64 with AC (identified by codes from the International Classification of Diseases, Ninth and Tenth Revisions) enrolled in the Truven MarketScan Commercial Claims and Encounters database (2009‐2015). We determined yearly prevalence, weighted to the national employer‐sponsored, privately insured population. Using competing risk analysis, we estimated event rates for portal hypertensive complications and estimated the association between AC and costs as well as admissions and readmissions. In 2015, 294, 215 people had cirrhosis and 105, 871 (36%) had AC. Mean age at AC diagnosis was 53.5 years, and 32% were women. Over the 7 years queried, estimated national cirrhosis prevalence rose from 0.19% to 0.27% ( P < 0.001) and for AC from 0.07% to 0.10% ( P < 0.001). Compared to non‐AC, AC enrollees were significantly more likely to have portal hypertensive complications at diagnosis and higher yearly cirrhosis and alcohol‐related admissions (25 excess cirrhosis admissions and 6.3 excess alcohol‐related admissions per 100 enrollees) as well as all‐cause readmissions. Per‐person costs in the first year after diagnosis nearly doubled for AC versus non‐AC persons (US 44, 835 versus 23, 319). Conclusion : In a nationally representative cohort of privately insured persons, AC enrollees were disproportionately sicker at presentation, were admitted and readmitted more often, and incurred nearly double the per‐person health care costs compared to those with non‐AC. (Hepatology 2018).